Clinical value of ankle brachial pressure index - Migdalski, Arkadiusz; Jawień, Arkadiusz (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2007)
Despite the technological progress and vascular imaging development measuring the systolic pressure at the ankle level has remain a standard part of the initial evaluation of patients with suspected peripheral arterial disease (PAD). The diagnosis of PAD may be easily confirmed with measurement of ankle to brachial pressure index (ABPI). All limitations of ABPI measurement must be taken under consideration to maintain high reliability of the test. In some patients with diabetes, renal insufficiency, or other diseases that cause vascular calcification, the vessels below the ankle level become non-compressible. Besides the validity in PAD diagnosing a reduced ABPI is a potent predictor of the risk of future cardiovascular events. Patients who should be considered for ABPI screening in the primary care include: all patients who have leg symptoms on exercise, all individuals between the age of 50-69 and those who have a cardiovascular risk factor (particularly diabetes or smoking), all patients age ł70 years regardless of risk factor status and all with a 10 years Framingham risk score 10-20%. An abnormal ABI (≤0,9; 1,4) identifies a high-risk population that needs aggressive risk factor modification and antiplatelet therapy to decrease the rate of cardiovascular death. Authors summarize clinical utility and limitations of ankle to brachial pressure index.